2017
DOI: 10.1002/slct.201701422
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Mixed Fluorinated Phenylthio‐ Subphthalocyanines

Abstract: Subphthalocyanines (SPcs), a platform of tripyrrolic macrocycles, offer a combination of optical and physical properties that make them highly applicable in a variety of fields. Incorporation of low‐symmetry elements allows for fine tuning of these properties by synthetic design. Herein, we report the synthesis of mixed fluorinated phenylthio‐ SPcs of the forms SPc(AnB3‐n) and SPc(AnC3‐n) where ‘A’ is tetrafluorobenzo‐, ‘B’ is 1,4‐bis(phenylthio)benzo‐, and ‘C’ is 1,4‐bis(phenylthio)naphtho‐, and n is an integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…During the last years, the synthesis of several unsymmetrical SubPc derivatives has been reported, including the preparation of low-symmetry SubPcs bearing peripheral ortho -substituents. 14,17,47–58…”
Section: Subphthalocyaninesmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last years, the synthesis of several unsymmetrical SubPc derivatives has been reported, including the preparation of low-symmetry SubPcs bearing peripheral ortho -substituents. 14,17,47–58…”
Section: Subphthalocyaninesmentioning
confidence: 99%
“…As a matter of fact, in the presence of both electron-donor (see for example ref. 16, 19, 20, 23, 35, 46, 47, 50, 51, 55, 105 and 118) and electron-withdrawing (see for example ref. 29, 32, 50, 52, 80, 114 and 122) peripheral substituents able to slightly extend the π-conjugation of the macrocycle, the Q band is commonly shifted to higher wavelengths with respect to the perhydrogenated SubPc derivative.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed cyclotrimerization of two different phthalonitriles to form a BsubPc hybrid has been shown to be a successful strategy in altering the optoelectronic and spectroscopic properties of BsubPc macrocycles. Within the literature, 3,4,5,6-tetrafluorophthalonitrile (TFPN) has been widely used as a participating precursor for many peripherally fluorinated BsubPc hybrids that exhibit red-shifted Q band absorption profiles functionalized via mixed cyclotrimerization yielding low-symmetry BsubPcs with fused 1,2,5-thiadiazole fragments, bay-position phenylthiolated BsubPc hybrids, pyrene-fused BsubPc hybrids, and 1,3-dithiole-2-one-fused BsubPc hybrids. , Despite these examples and other reports investigating mixed cyclotrimerization to achieve diverse functionalization patterns and unique optoelectronic properties, mixed and/or low-symmetry BsubPcs and BsubNcs have received significantly less attention (Web of Science hits: 19 for mixed boron subphthalocyanines, 2 for mixed boron subnaphthalocyanines, 14 for low-symmetry boron subphthalocyanines, and 2 for low-symmetry boron subnaphthalocyanines; Figure e) than the C 3 v -symmetric boron subphthalocyanines (224 hits) and boron subnaphthalocyanines (29 hits). There exists a single example in which a C s -symmetric BsubPc hybrid has been implemented into an organic electronic application.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that electronic absorption and emission profiles are highly tunable across the visible region through variation of peripheral F-atoms and aromaticity. Subsequently, it was shown that further modulation and tunability of photophysical properties could be achieved through inclusion of peripheral electron-donating thioethers [21] or fused thiadazole rings [22]. When applied as fluorescent imaging probes in vitro in MDA-MB-231 breast tumor cells, the presence of peripheral fluorine proved to be imperative; there was a marked increase in intracellular fluorescence from subphthalocyanine (#F = 0) to tetrafluorosubphthalocyanine (#F = 4).…”
Section: Introductionmentioning
confidence: 99%